2018
DOI: 10.1113/jp276424
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic loss of dynamin‐related protein 1 impairs synaptic vesicle release and recycling at the mouse calyx of Held

Abstract: Key points This study characterizes the mechanisms underlying defects in synaptic transmission when dynamin‐related protein 1 (DRP1) is genetically eliminated. Viral‐mediated knockout of DRP1 from the presynaptic terminal at the mouse calyx of Held increased initial release probability, reduced the size of the synaptic vesicle recycling pool and impaired synaptic vesicle recycling. Transmission defects could be partially restored by increasing the intracellular calcium buffering capacity with EGTA‐AM, implyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 83 publications
(206 reference statements)
1
17
0
Order By: Relevance
“…Targeted viral infection. CNS injection of neonatal mice followed protocols described previously (Singh et al, 2018). Briefly, 1-d-old (P1) mice were chilled on ice for Ͼ5 min until unresponsive, then fixed on a stereotaxic surgery platform.…”
Section: Mouse Brain Slice Preparation and Imaging At The Calyx Of Heldmentioning
confidence: 99%
“…Targeted viral infection. CNS injection of neonatal mice followed protocols described previously (Singh et al, 2018). Briefly, 1-d-old (P1) mice were chilled on ice for Ͼ5 min until unresponsive, then fixed on a stereotaxic surgery platform.…”
Section: Mouse Brain Slice Preparation and Imaging At The Calyx Of Heldmentioning
confidence: 99%
“…Mitochondrial dysfunction is implicated in the pathological progression of OA via a number of pathways, including oxidative stress, cartilage matrix synthesis and degradation disorder, cytokine mediated inflammatory response activation and chondrocyte death (10,11). Recent studies have highlighted an important role of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission in mitochondrial homeostasis (12,13). Mechanistically, excessive mitochondrial fission contributes to mitochondrial dysfunction as indicated by loss of mitochondrial DNA integrity, reduction in ATP generation, mitochondrial ROS outburst, and loss of mitochondrial membrane potential (13).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted an important role of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission in mitochondrial homeostasis (12,13). Mechanistically, excessive mitochondrial fission contributes to mitochondrial dysfunction as indicated by loss of mitochondrial DNA integrity, reduction in ATP generation, mitochondrial ROS outburst, and loss of mitochondrial membrane potential (13). Furthermore, excessive fission triggers mitochondrial permeability transition pore (mPTP) opening via regulating voltage-dependent anion channel 1 (VDAC1) and hexokinase 2 (HK2), which plays a critical role in cell death (14).…”
Section: Introductionmentioning
confidence: 99%
“…A previous report indicated that Drp1-dependent division is required for efficient mitochondrial transport and for maintaining synaptic function 31 33 . Hence, Drp1 deficiency and reduced ATP production may decrease the capability of mitochondrial movement toward synaptic terminals and lead to mitochondrial depletion in axon terminals as subsequent neurodegeneration 32 , 34 , 35 . Given that we found decreased Drp1 expression in Fen-treated primary neurons, we next investigated mitochondrial morphology and mass in neurites.…”
Section: Resultsmentioning
confidence: 99%